Strengthening Al-Zn-Mg Alloys via Ultra-Fine Lamella Structures Containing a High Density of Dislocations and Clusters - Yonggui Qin (Metals, 2019)
A new method of thermo-mechanical processing has been designed by introducing pre-aging before general cold rolling for an Al-Zn-Mg alloy. This process results in an increase of 200 MPa in yield strength compared to that of the peak-aged samples. The microstructures were examined by transmission electron microscope and X-ray diffraction. It has been found that the enhanced strength is mainly contributed to by ultra-fine lamella structures containing a high density of dislocations pinned by nanoprecipitates. Extra strength is provided by the “interlocking„ of precipitates and dislocations. Fractographic features analysis shows that crack propagation along the interface of the lamella structures is the direct reason for resulting in fracture, due to intra-granular strength exceeding grain boundary cohesion.